Linearisation of asymmetrical Doherty amplifier by the even-order non-linear signals. Issue 8 (2nd August 2016) - Maleš-Ilić, Nataša; Atanasković, Aleksandar; Blau, Kurt; Hein, Matthias
ABSTRACT: This paper considers the linearisation of an asymmetrical two-way Doherty amplifier by the method that uses the second harmonics and fourth-order non-linear signals for linearisation. These even-order signals for linearisation are extracted at the output of the peaking amplifier, adjusted in amplitude and phase and injected at the input and output of the carrier amplifier transistor in the Doherty configuration. The effect of linearisation has been experimentally confirmed on a fabricated asymmetrical Doherty amplifier with the additional circuit for linearisation. The suppression of the third-order intermodulation products has been carried out for two-tone test, 64QAM and WCDMA digitally modulated signals in a range of signal power.